Wear behavior of graphite self-lubricating Babbitt alloy composite coating on 20 steel prepared by laser cladding. (November 2022) - Xu, T.Z.; Zhang, S.; Wang, Z.Y.; Zhang, C.H.; Zhang, D.X.; Wang, M.; Wu, C.L.
Highlights: A novel self-lubricating Babbitt alloy composite coating was designed. A comparable study was performed between Babbitt coating and self-lubricating composite coating. Nano-indentation behavior of the self-lubricating Babbitt alloy composite coating was studied. Wear behavior and mechanism of the self-lubricating Babbitt alloy composite were investigated. Abstract: A tin-based Babbitt self-lubricating composite coating was fabricated on 20 steels substrate by laser cladding through the mixed powders of nickel-plated graphite (Ni-Gr) composite powders and Babbitt alloy powders, aiming at improving wear resistance of Babbitt alloy coating. The results showed that the self-lubricating phase (graphite) coated by the nickel still remained elemental in the composite coating after laser cladding. Both Babbitt coating and Ni-Gr/Babbitt composite coating were uniform and density, without pore, cracks or any other defects, and were mainly composed of α-Sn solid solution phase, Cu6 Sn5 and SnSb precipitated phases. The grains were obviously refined for the composite coating due to the heterogeneous nucleation. The nano-hardness ( H ), nano-hardness/elastic modulus ( H / E ) and ( H 3 / E 2 ) for the Ni-Gr/Babbitt composite coating were 1.15 GPa, 0.0137 and 1.9 × 10 −4, which was much higher than that of the Babbitt coating with the value of 0.57 GPa, 0.0068 and 2.3 × 10 −5 . With respect to the increase in the nano-hardness, Ni-Gr/Babbitt composite coating also exhibited a low friction coefficient and wear rate with the value of 0.301 and 6.31 × 10 −6  mm 3 /N∙m. The addition of Ni-Gr can effectively improve the self-lubricating and wear behavior of Babbitt alloys.